Two-item PROMIS® global physical and mental health scales - Ron D. Hays; Benjamin D. Schalet; Karen L. Spritzer; David Cella (SpringerOpen, 2017)
Abstract Background Self-reports of health provide useful information about function and well-being that can improve communication between patients and clinicians. Global health items provide summary information that are predictive of health care utilization and mortality. There is a need for parsimonious global health scales for use in large sample surveys. This study evaluates the reliability and validity of brief measures of global physical health and mental health in the Patient Reported Outcomes Measurement and Information System (PROMIS®) project. Methods A total of 21,133 persons included in the PROMIS development sample: 52% female; 82% White, 9% Black, 9% Hispanic; median age of 50 years. We identified two global physical health items (GPH-2) and two global mental health items (GMH-2) with highest discrimination parameters and compared their reliabilities and construct validity to that of the original 4-item scales (GPH-4 and GMH-4) and a single global health item (Global01). Results Internal consistency reliability was 0.73 for the GPH-2 (versus 0.81 for the GPH-4) and 0.81 for the GMH-2 (versus 0.86 for the GMH-4). Marginal reliabilities were 0.55 for Global01, 0.70 for GPH-2, 0.79 for GPH-4, 0.80 for GMH-2, and 0.86 for GMH-4. The product-moment correlation between the GPH-2 and GPH-4 was 0.94 and between GMH-2 and GMH-4 was 0.97. The 2-item and 4-item versions of the scales had similar correlations with PROMIS domain scores, the EQ-5D-3L and comorbidities, but the 4-item scales were more strongly correlated with these measures. Conclusions Adding a single item to a large cross-sectional population survey can cost as much as $100,000. The 2-item variants of the PROMIS global health scales reduce the cost of use on national surveys by 50%, a substantial cost savings. These briefer scales are also more practical for use in clinical practice. The 2-item versions of the PROMIS global health scales display adequate reliability for group comparisons and their associations with other indicators of health are similar to that of the original 4-item scales. The briefer scales are psychometrically sound and reduce burden of survey administration.